Current trends and hotspots in drug-resistant epilepsy research: Insights from a bibliometric analysis - Ni, Xiao-Jun; Zhong, Han; Liu, Yang-Xi; Lin, Hou-Wen; Gu, Zhi-Chun (Frontiers in Neurology, 2022)
Background Drug-resistance is a significant clinical issue in persons with epilepsy. In the past few years, many studies have been published investigating the management of drug-resistant epilepsy (DRE); however, no systematic and quantitative evaluation of this research has been performed. Therefore, a bibliometric analysis was conducted to demonstrate the current status of DRE research and to reflect the trends and hotspots within the field. Methods We retrieved publications on DRE published between 2011 and 2021 from the Science Citation Index Expanded of the Web of Science Core Collection. All articles related to DRE were included in this study. VOSviewer, R software, and CiteSpace were used to perform bibliometric research. Results A total of 3,088 original articles were included in this study. The number of publications on DRE has continued to increase over the past 11 years. The USA published the most papers with the highest number of citations and H-index. The National Institutes of Health and the University of Toronto were the most prolific funding agency and affiliation, respectively. Epilepsy & Behavior and Epilepsia ranked first as the most prolific and co-cited journals, respectively. The keywords “cannabidiol”, “neuromodulation”, “seeg” and “perampanel” revealed recent research hotspots. The top 100 most cited papers were classified into eight main topics, of which pharmacotherapy, disease mechanisms/pathophysiology, and neuromodulation were the three most important topics. Conclusions This analysis of bibliometric data demonstrated that DRE has always been a topical area of research. The mechanisms of epilepsy and therapies have been the focus of DRE research, and innovative antiseizure medications and surgical approaches are fast-developing research trends.